Patellar Tendon Rupture after Lateral Release without Predisposing Systemic Disease or Steroid Use. (15th April 2015) - De Giorgi, S.; Notarnicola, A.; Vicenti, G.; Moretti, B.
Abstract : Arthroscopic technique for lateral release is the most widely used procedure for the correction of recurrent dislocations of the patella. In the relevant literature, several complications of lateral release are described, but the spontaneous patellar tendon rupture has never been suggested as a possible complication of this surgical procedure. Patellar tendon rupture is a rather infrequent and often unilateral lesion. Nevertheless, in case of systemic diseases (LES, rheumatoid arthritis, and chronic renal insufficiency) that can weaken collagen structures, bilateral patellar tendon ruptures are described. We report a case of a 24-year-old girl with spontaneous rupture of patellar tendon who, at the age of 16, underwent an arthroscopic lateral release for recurrent dislocation of the patella. This is the first case of described spontaneous patellar tendon rupture that occurred some years after an arthroscopic lateral release.